(3JbfjGJ hJCKjQGJs - (3CSeGA(B, (3GdLjhTjs ((3GdEeGQGJ GdYQHjI GdeJMOI(B;(3GdLeghQjI GddHfGfjI(B:s (3OGQ GdcJGH GdLGeYj(B,s, 2019)
(3jhVM gPG GdcJGH Cf GdUhQI JYO eGOI KGHKI hQFjSjI aj GdCNHGQ GdJdaRjhfjI MjK jJe GYJeGO GdYOjO ef hSGFd GdEYdGe Ydi GdUhQI GdJdaRjhfjI dJhVjM GdNHQ hYQVg HUhQI hGbYjI, ceG Cf GdhbJ GdeNUU ddUhQ aj fTQGJ GdCNHGQ aj EQJaGY eSJeQ hJRjO GdUhQI ef GSJjYGH GdeYdheGJ hJPcQgG MjK JJCKQ GdPGcQI HGdUhQI CcKQ ef GdUhJ, dCf GdUhQI GdHUQjI CcKQ QShNG haQVG dfaSgG ef GdUhQI GdCNQi , aGdUhQ dZI JSJgOa JhUjd GdeYdheGJ(B. (3hSjHjf Cf HYV GdGNJHGQGJ GdSeYjI hGdHUQjI bO CcOJ Cf GSJjYGH GdaQO ddeYdheGJ jROGO YfO GSJNOGe GdUhJ hGdUhQI aj hbJ hGMO hCf eOI GdGMJaGX HgPg GdeYdheI JWhd, eeG jDcO OhQgG aj GdYedjI GdeYQajI GdJj JSge aj EOQGc hage hJPcQ GdCNHGQ , agj JYed Ydi LPH GfJHGg GdeTGgO EdjgG , HeG jOYe Jahb GdUhQI hjLYdgGq CcKQ EbfGYG ef GdcdeI, HGdGVGaI Gdi GMJhGAgG Ydi GdGdhGf GdJj JSGYO GdeTGgO aj GSJjYGH GdeYdheGJ hJegO dGOQGc hage GdeYdheI Ke JSGYO Ydi JPcQgG HYO Pdc(B.s
Keywords: (3GdUhQI GdJdaRjhfjI(B: (3GdJbfjGJ hGdJCKjQGJs; (3GdcGejQG GdJdaRjhfjIs; (3hSGFd GdGJUGd GdeQFjIs